(untitled) (Bangladesh Journal of Medical Education, 2019)
This descriptive cross sectional study was carried out from July 2015 to June 2016 to identify the teachers’ views regarding the suggested responsibilities of concerned authorities in faculty development (FD )in undergraduate medical education of Bangladesh. A semistructured self-administered questionnaire was used for collecting data from 103 teachers of eight Government and Non- Government medical colleges located within and outside Dhaka. They agreed with the different suggested role of the departments, institutes, teachers’ associations, Director Medical Education (DME), and Ministry of Health & Family Welfare (MOHFW) for FD. Among the suggestions the most agreed roles were ’Make an outline for participation of CME & CPD’ for promotion by MOHFW (80%); ‘Arrangement of CME & CPD’ by the institutes (79%); ‘Arrangement of CME & CPD’ by the teachers association (76%); ‘Supervision of faculty development’ by the DME (76%); ‘Distribution of personal review form (54%)’ , ‘Collection of personal review form (54%)’ and ’Time management of faculty development(54%)’ by the departments. It is recommended that the concerned authorizes should play their own role appropriately for proper implementation of the FD. Bangladesh Journal of Medical Education Vol.10(2) 2019: 2-5